2021
DOI: 10.4239/wjd.v12.i7.1010
|View full text |Cite
|
Sign up to set email alerts
|

Current cancer therapies and their influence on glucose control

Abstract: This review focuses on the development of hyperglycemia arising from widely used cancer therapies spanning four drug classes. These groups of medications were selected due to their significant association with new onset hyperglycemia, or of potentially severe clinical consequences when present. These classes include glucocorticoids that are frequently used in addition to chemotherapy treatments, and the antimetabolite class of 5-fluorouracil-related drugs. Both of these classes have been in use in cancer thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 102 publications
0
5
0
12
Order By: Relevance
“…There are several cases of autoimmune diabetes with the treatment of immune checkpoint inhibitors. It is reported that hyperglycemia is associated with checkpoint blockade and can occur in up to approximately 5% of treated patients [ 149 ]. Furthermore, in patients with diabetes, the use of immune checkpoint blockades can worsen glucose control, in particular, PD-1/PD-L1 therapies, as PD-L1 is expressed on pancreatic beta cells.…”
Section: Metabolism and Immune-related Adverse Events (Iraes) Associated With Immune Checkpoint Blockade Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…There are several cases of autoimmune diabetes with the treatment of immune checkpoint inhibitors. It is reported that hyperglycemia is associated with checkpoint blockade and can occur in up to approximately 5% of treated patients [ 149 ]. Furthermore, in patients with diabetes, the use of immune checkpoint blockades can worsen glucose control, in particular, PD-1/PD-L1 therapies, as PD-L1 is expressed on pancreatic beta cells.…”
Section: Metabolism and Immune-related Adverse Events (Iraes) Associated With Immune Checkpoint Blockade Therapymentioning
confidence: 99%
“…While the onset of hyperglycemia may not require treatment cessation, in some cases, immune checkpoint blockade can result in rapid ketosis. Thus, monitoring glucose levels in patients undergoing treatment is warranted [ 149 ]. These studies begin to provide insight into irAE that can develop due to immune checkpoint blockade therapy for patients with autoimmune disease, providing a foundation to continue to examine alternative treatment regimens and treatments to reduce irAE for cancer patients.…”
Section: Metabolism and Immune-related Adverse Events (Iraes) Associated With Immune Checkpoint Blockade Therapymentioning
confidence: 99%
“…Aufgrund ihres zunehmenden Einsatzes in der modernen onkologischen Therapie verdienen insbesondere Immuncheckpointinhibitoren Aufmerksamkeit. Wenngleich selten (0,2–4,9 %), manifestiert sich der autoimmun vermittelte Diabetes hier mit sehr variabler Latenz oft hochakut und in 78 % der Fälle mit einer Ketoazidose [ 31 , 83 ]. Besondere Risikofaktoren für Hyperglykämien sind auch eine Glukokortikoidbehandlung [ 41 , 77 ] sowie enterale und parenterale Ernährung [ 17 , 39 , 52 , 71 ].…”
Section: Klinische Relevanz Der Nebendiagnose Diabetes Mellitusunclassified
“…Diabetes mellitus Besonderheiten Künstliche Ernährung Enteral 20–35 % [ 28 , 71 ] Negativer Prognosemarker; abhängig von Zusammensetzung (Kohlenhydrate, Ballaststoffe), Applikation (Bolus, diskontinuierlich, kontinuierlich; gastral vs. jejunal) und patientenindividuellen Faktoren (akute Erkrankung, Magenentleerungsstörung); reduziert durch kohlenhydratarme Lösungen [ 10 , 28 , 52 , 71 ] Parenteral > 50 % [ 17 , 39 , 71 ] Negativer Prognosemarker; abhängig von Zusammensetzung (Glukose, Lipidtyp, Glutamin), Timing (früher vs. verzögerter Beginn), Kombination mit enteraler Ernährung und patientenindividuellen Faktoren (akute Erkrankung; [ 17 , 39 , 71 ]) Medikamentöse Therapien Glukokortikoide Neue oder verschlechterte Hyperglykämie: 34–94 % [ 31 , 41 , 77 , 83 ] Hyperglykämie in 32,3 % und Diabetes mellitus in 18,6 % aller Patienten ohne vorbestehenden Diabetes [ 41 ]; frühe Manifestation nach Therapiebeginn (94 %), milde und selten komplikationsreiche Ausprägung, prinzipiell reversibel Risiko abhängig von Präparat, Dosis, Therapiedauer, Indikation (rheumatische Erkrankungen vs. Transplantation vs. Onkologie) und patientenindividuellen Faktoren (Alter, Gewicht, Familienanamnese Diabetes, ethnische Zugehörigkeit, vorbekannte Glukoseintoleranz; [ 77 ]) SSRI Die Einnahme von SSRI erhöht das Risiko für die Entwicklung eines Diabetes mellitus um 38 % [ 82 ] Kalzineurininhibitoren: Tacrolimus, Sirolimus Medikation mit Tacrolimus erhöht die Inzidenz des insulinabhängigen Diabetes mellitus signifikant von 4,5 % auf 10,4 % [ 20 ] Die diabetogene Wirkung von Sirolimus (besonders 5–10 Jahre nach Transplantation) und Tacrolimus (besonders 1–3 Jahre nach Transplantation) ist eine Ursache der organunabhängig erhöhten Diabetesinzidenz nach solider Organtransplantation [ 20 , 30 ] Tumorspezifische medikamentöse Therapie 5‑FU und Analoga …”
Section: Klinische Relevanz Der Nebendiagnose Diabetes Mellitusunclassified
“…A két kórforma specifikus terápiája közti összefüggés fordítva is fennáll. Az antineoplasztikumok számottevő része, saját felmérésünk alapján minden harmadik hatóanyag, szignifikánsan ront hatja a meglévő szénhidrátanyagcsere-zavarokat, sőt elhúzódó hyperglykaemiát, praediabetest (IR, IFG, IGT) vagy akár manifeszt cukorbetegséget okozhat [14][15][16][17][18]. A glükokortikoidok és egyéb endokrin készítmények ismert diabetogén effektusai mellett egyre több hagyományos citosztatikumról és modern célzott biológiai terápiáról bizonyosodik be, hogy akár súlyosan megzavarhatják a glükózanyagcserét.…”
Section: áTfedések Az Antineoplasztikus éS Az Antidiabetikus Terápiákbanunclassified